Rapid screening of foot-and-mouth disease virus antibody secreting hybridomas by immunodot - VENKATARAMANAN, R; PATTNAIK, B; MOHANTY, J; RAI, D V; MUKHOPADHYAY, A K (The Indian Journal of Animal Sciences, 2013)
Immunodot assay using a microfiltration device-enzyme- linked immunofiltration assay- was used to screen hybridoma supernatants from fusion plates for the presence of antibodies to foot-and-mouth-disease virus. Freshly harvested infected cell culture supernatant, as the source of virus, was suitable for the assay. All immunodol-positive supernatants were reactive with complete virus particles (1465 particle) in ELISA. Though immunodot assay was as specific as ELISA, it helped in maximizing the antigen-antibody reaction in the supernatants giving lesser OD values in ELISA. Moreover, the assay system was very much time saving as it dispersed with long incubations and washing steps of ELISA.